2012
DOI: 10.1115/1.4005776
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Mapping and Exploration of Configuration Space

Abstract: We describe a graphics processing unit (GPU)-based computational platform for six-dimensional configuration mapping, which is the description of the configuration space of rigid motions in terms of collision and contact constraints. The platform supports a wide range of computations in design and manufacturing, including three- and six-dimensional configuration space obstacle computations, Minkowski sums and differences, packaging problems, and sweep computations. We demonstrate dramatic performance improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Other applications show the computation of workspaces of parallel linkages, like the 4-bar chain [23]. Recently Nelaturi et al showed that group morphology can be used to determine the accessible positions and orientations of a weld gun [24].…”
Section: Group Morphology and Spectral Methodsmentioning
confidence: 99%
“…Other applications show the computation of workspaces of parallel linkages, like the 4-bar chain [23]. Recently Nelaturi et al showed that group morphology can be used to determine the accessible positions and orientations of a weld gun [24].…”
Section: Group Morphology and Spectral Methodsmentioning
confidence: 99%
“…For 5-axis machining applications, one of the six DOF for rotation around the tool axis is deemed redundant and the problem is simplified by assuming simple shapes for the rotating tool's closure such as a flat/ball-end cylinders, approximating reachability by visibility, and so on [34][35][36][37][38][39][40][41]. However, the computations can be dramatically simplified by sampling-based approximations [42]. It has been shown that collision measures can be obtained as convolutions of indicator functions of the two bodies [43], and computed rapidly via fast Fourier transform (FFT) if these functions are sampled over uniform grids (i.e., voxelization) [44].…”
Section: Related Workmentioning
confidence: 99%
“…Rather, they are often expressed as set constraints, i.e., statements in the language of sets (e.g., in terms of affine transformations, Boolean operations, and containment) rather than the language of realvalued functions used for (in)equality constraints in TO. A broad class of inverse problems in practical design and manufacturing reduce to solving set constraints formulated in the configuration space of rigid motions [6,[65][66][67].…”
Section: Design For Motion-related Constraintsmentioning
confidence: 99%
“…For instance, if we impose a constraint on the maximal stress as in (6), we cannot define a realistic TSF due to stress concentration. The simplest model of stress concentration yields an infinite maximal stress σ Ω (x) ∼ O( −0.5 ) near an infinitesimal radius of curvature → 0 + , hence T i (x; Ω) ∼ O( −3.5 ) → +∞ when defined for the maximal stress as in (6). In practice, one can alleviate this issue by using a volumetric integral (e.g., the p−norm) of 12 This is the actual motivation behind using a volumetric measure of the inclusion in the denominator of (75) to normalize volumetric measures in the numerator.…”
Section: Limitations Of Sensitivity-based Explorationmentioning
confidence: 99%